2014
DOI: 10.1603/me14029
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Genetic Investigation of the Egg and First-Instar Larva of an Egg-Laying Population of <I>Blaesoxipha plinthopyga</I> (Diptera: Sarcophagidae), a Species of Forensic Importance

Abstract: Flies in the family Sarcophagidae incubate their eggs and are known to be ovoviviparous (i.e., ovolarviparous), but a laboratory-maintained colony of Blaesoxipha plinthopyga (Wiedemann) deposited clutches of viable eggs over 10 generations. A description of the egg and first-instar larva of this species is provided along with genetic data (genome size and cytochrome oxidase I sequences). The egg is similar to previously described eggs of other Sarcophagidae but differs in the configuration of the micropyle. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The final assembly, which consisted of 42,093 scaffolds (522 Mbp), was used for gene prediction and to establish the draft genome for S. bullata . This is 12% smaller than the predicted genome (593 Mbp, Pimsler et al , 2014), a common result for first assembly of genomes (Anstead et al , 2016; Benoit et al , 2016; Attardo et al , 2014).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The final assembly, which consisted of 42,093 scaffolds (522 Mbp), was used for gene prediction and to establish the draft genome for S. bullata . This is 12% smaller than the predicted genome (593 Mbp, Pimsler et al , 2014), a common result for first assembly of genomes (Anstead et al , 2016; Benoit et al , 2016; Attardo et al , 2014).…”
Section: Resultsmentioning
confidence: 76%
“…Different assembly protocols resulted in short read assemblies ranging in size from 230 million bases to 3.8 billion bases, i.e. , 39–640% of the 593 million bases measured by flow cytometry (Pimsler et al , 2014), divided among 2n = 12 chromosomes (Bultmann and Mezzanotte 1987). Reapr was used to examine the quality of assembly and trim the short-read assemblies at sites of likely misassembly, thus resulting in substantive changes to the chosen assembly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pimsler et al (2019) identified genes associated with intraguild predator, C. rufifacies . The genetic data and genome size was also analyzed for B. plinthopyga , finding that the female genome was larger than the male (Pimsler et al, 2014). The genome size was studied in different populations of developing C. macellaria , one that was selected for fast development and one for slow development, which found that mean genome size did not change (Hjelman et al, 2020).…”
Section: Forensic Entomological Literature In the Southwestmentioning
confidence: 99%
“…One of the particularities of this family is its ovoviviparous biology (at least for the vast majority of species -see Bordas et al (2007) [8] and Pimsler et al (2014) [9]), the female sarcophagids deposit first instar larvae on the colonization substrate and, this characteristic can enable pioneering in the colonization of the substrate [10,11]. Of the substrates used by sarcophagids, their role in colonizing decomposing non-human vertebrate carcasses [e.g.…”
Section: Introductionmentioning
confidence: 99%